Combinatorial Approach to Chiral Tris‐ligated Carbophilic Platinum Complexes: Application to Asymmetric Catalysis. Issue 23 (22nd April 2014) - Pradal, Alexandre; Gladiali, Serafino; Michelet, Veronique; Toullec, Patrick Y.
Abstract A straightforward methodology for the synthesis of libraries of chiral tris‐ligated cationic platinum complexes and their in situ evaluation as asymmetric carbophilic catalysts in a model domino hydroarylation/cyclization reaction of a 1, 6‐enyne was developed. A catalyst‐generation process based on a combination of a monodentate and a bidentate phosphorus ligand allowed the formation of 108 chiral complexes. One‐pot screening of the stereoinduction obtained with this library in a test domino addition/cyclization reaction validated this approach and stressed the key role played by the monodentate ligand partner in obtaining high enantioselectivities. In the case of two challenging substrate/nucleophile combinations, the combinatorial approach resulted in a significant gain in enantioselectivity.